Best Practice : Honours and Coursework Dissertation Supervision : Final Report. - Roberts, Lynne (Office for Learning and Teaching, 2015)
Final report of a Teaching Fellowship at Curtin University. The issue addressed in this Fellowship was the paucity of material available to support supervisors of dissertation students in coursework degrees (undergraduate, honours and masters by coursework) in Australian universities. Most universities provide policy and procedural documents relating to dissertation supervision, but limited training in the practice of supervision within coursework degrees. Fellowship activities focused on the identification, documentation and dissemination of best practice in dissertation supervision in coursework degrees. The overarching approach to the fellowship was to work collaboratively with interested academics within the higher education system to identify, develop and disseminate good practice in coursework dissertation supervision.